Antibacterial activity of salvia officinalis L. against periodontopathogens: An in vitro study. (June 2020) - Mendes, Filipe Santos Ferreira; Garcia, Letícia Matanovich; Moraes, Thais da Silva; Casemiro, Luciana Assirati; Alcântara, Clauber Barbosa de; Ambrósio, Sérgio Ricardo; Veneziani, Rodrigo Cássio Sola; Miranda, Mayker Lazaro Dantas; Martins, Carlos Henrique Gomes
Abstract: Being aware of the remarkable antimicrobial potential of S. officinalis L., we aimed to evaluate the antimicrobial activity of the S. officinalis dichloromethane crude extract (SOD), dichloromethane-soluble fractions (SODH and SODD), SODD subfractions (SODD1 and SODD2), and pure substances (manool, salvigenin, and viridiflorol) against periodontopathogens. This bioassay-guided study comprises five antimicrobial tests—determination of the Minimum Inhibitory Concentration (MIC), determination of the Minimum Bactericidal Concentration (MBC), determination of the antibiofilm activity, construction of the Time-kill curve (determination of Bactericidal Kinetics), and determination of the Fractional Inhibitory Concentration Index—on six clinical bacterial isolates and three standard bacterial strains involved in periodontal disease. SOD has moderate activity against most of the tested bacteria, whereas SODD1, SODH1, SODH3, and manool afford the lowest results. The Porphyromonas gingivalis (ATTC and clinical isolate) biofilm is considerably resistant to all the samples. In association with chlorhexidine gluconate, only SODH1 exerts additive action against P. gingivalis (clinical isolate). Therefore, SODH1 and manool are promising antibacterial agents and may provide therapeutic solutions for periodontal infections. Highlights: S. officinalis crude extract had moderate action against all the bacteria tested. Subfractions the bioguided study (SODD1, SODH1, SODH3), and manool compound proved to be promising antimicrobial agents. The secondary metabolites of S. officinalis may provide therapeutic solutions for periodontal infections.